Tales of mystery and imagination - Poe, Edgar Allan, 1809-1849. (London : Bloomsbury, 2009)
A modern selection of Poe's best stories including The Pit and the Pendulum, The Tell-Tale Heart, and The Murders in the Rue Morgue.
Reprint. Originally published: 1902.
Young Adult.
Young Adult
Keywords: Detective and mystery stories, American; Horror tales, American; Short stories